Pharmacokinetics, Pharmacodynamics and Antiviral Efficacy of the MEK Inhibitor Zapnometinib in Animal Models and in Humans - Koch-Heier, Julia; Schönsiegel, Annika; Waidele, Lara Maria; Volk, Julian; Füll, Yvonne; Wallasch, Christian; Canisius, Sebastian; Burnet, Michael; Planz, Oliver (Frontiers in Pharmacology, 2022)
The mitogen-activated protein kinase (MEK) inhibitor zapnometinib is in development to treat acute viral infections like COVID-19 and influenza. While the antiviral efficacy of zapnometinib is well documented, further data on target engagement/pharmacodynamics (PD) and pharmacokinetics (PK) are needed. Here, we report zapnometinib PK and PD parameters in mice, hamsters, dogs, and healthy human volunteers. Mice received 25 mg/kg/day zapnometinib (12.5 mg/kg p. o. twice daily, 8 h interval). Syrian hamsters received 30 mg/kg (15 mg/kg twice daily) or 60 mg/kg/day once daily. Beagle dogs were administered 300 mg/kg/day, and healthy human volunteers were administered 100, 300, 600 and 900 mg zapnometinib (once daily p. o.). Regardless of species or formulation, zapnometinib maximum plasma concentration (Cmax) was reached between 2–4 h after administration with an elimination half-life of 4–5 h in dogs, 8 h in mice or hamsters and 19 h in human subjects. Doses were sufficient to cause up to 80% MEK inhibition. Across all species approximately 10 μg/ml zapnometinib was appropriate to inhibit 50% of peripheral blood mononuclear cells (PBMC) MEK activity. In mice, a 50%–80% reduction of MEK activity was sufficient to reduce influenza virus titer in the lungs by more than 90%. In general, while >50% MEK inhibition was reached in vivo at most doses, 80% inhibition in PBMCs required significantly higher doses and appeared to be the practical maximal level obtained in vivo. However, the period of reduced phosphorylated extracellular-signal regulated kinase (pERK), a measure of MEK inhibition, was maintained even after elimination of zapnometinib from plasma, suggesting a sustained effect on MEK consistent with regulatory effects or a slow off-rate. These data suggest a target plasma Cmax of at least 10 μg/ml zapnometinib in further clinical studies.